Análise da aplicação do controle estatístico de processo segundo as percepções dos usuários do setor de autopeças - Soriano, Fabiano Rodrigues (2015)
The Statistical Process Control (SPC) is recognized in the literature as one of the main tools for controlling and improving the quality and productivity. The control chart is a central element of the SPC; and these, statistical tools whose efficiency depends on certain skills and organizational behavior. With regard to the results to the organization, it is observed that the use of control charts can be divided into two groups: those that can be directly attributed to reduced variability called hard; and those associated with the motivational aspects, or organic, called Soft. Despite the arguments in favor of SPC survey, a study conducted in the automotive sector shows that about 70% of companies have some difficulty in conducting their activities related to the SPC. On this, the literature indicates that factors related to methodological, statistical and managerial aspects of control charts of the implementation process are conditions for the success of a structured plan of implementation of the SPC. Given this situation, it is objective of this thesis contribute to an effective use of control charts by national companies, and to advances in research. To this end, we opted for a field survey to capture and describe the perceptions of experts who use control charts and working in the automotive industry. The field research was structured in three basic dimensions - statistics, methodology and management, and the results achieved by the use of the SPC, divided into Soft and Hard. The method used was based on a survey, which has a population of interest was the managers of SPC programs that use the control charts for more than 01 years in the auto parts industry. This survey was sent to 98 individuals in the population of interest, identified in the Official Guide Auto parts Industry (2014), which resulted in 37 questionnaires and valid for analysis. The results of this field research validated the hypotheses in part the theoretical framework, but showed, besides the complexity and importance of methodological and managerial aspects in the implementation of the SPC, there is a significant gap between theory and practice. This may partly be explained by the dissonance between the main scientific advances in the field, especially in the statistical aspects, and the controversies about the real benefits of SPC program. As a result of this thesis is recommended that field research has been done for that to report real success stories of the SPC; whose cases are examined in depth so that good practice is disseminated in the academic environment.